2020
DOI: 10.1002/mrc.4999
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop NMR analysis of piperazine‐based drugs hyperpolarised by SABRE

Abstract: Piperazine-based drugs, such as N-benzylpiperazine (BZP), became attractive in the 2000s due to possessing effects similar to amphetamines. Herein, BZP, in addition to its pyridyl analogues, 2-, 3-, and 4-pyridylmethylpiperazine (2-PMP, 3-PMP, and 4-PMP respectively) was subjected to the hyperpolarisation technique Signal Amplification By Reversible Exchange (SABRE) in order to demonstrate the use of this technique to detect these piperazine-based drugs. Although BZP was not hyperpolarised via SABRE, 2-PMP, 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Solvent suppression based on gradient pulse sequence [97,107] Homo-decoupling method using different pure-shift methods [108] Addition of salts as chemical shift agents to peptide sample [109] Hyperpolarization methods (SABRE) [110][111][112][113][114] Figure 11 shows that spectral resolution can be increased using various pulse sequences and the homo-decoupling method, which is another technique commonly used in high-field NMR spectroscopy. Moreover, benchtop NMR spectrometers with gradient coils can be used to increase signal sensitivity through the programming of various pulse sequences [108].…”
Section: Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Solvent suppression based on gradient pulse sequence [97,107] Homo-decoupling method using different pure-shift methods [108] Addition of salts as chemical shift agents to peptide sample [109] Hyperpolarization methods (SABRE) [110][111][112][113][114] Figure 11 shows that spectral resolution can be increased using various pulse sequences and the homo-decoupling method, which is another technique commonly used in high-field NMR spectroscopy. Moreover, benchtop NMR spectrometers with gradient coils can be used to increase signal sensitivity through the programming of various pulse sequences [108].…”
Section: Techniquementioning
confidence: 99%
“…In this study, improved resolution resulted in more accurate quantitative analysis, which allowed the researchers to better understand peptide reaction kinetics. Although they are not universally applicable to all samples, hyperpolarization methods can be used for the enhancement of low-field NMR signals [110][111][112][113][114]. Hyperpolarization generates a population distribution that is significantly larger than that dictated by the Boltzmann distribution at thermal equilibrium.…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The potential of benchtop NMR for uncovering drug falsification was demonstrated by Assemat et al [12] in their analysis of the most common falsified medicines: erectile dysfunction and anti-malarial medicines. Fifteen seized falsified erectile dysfunction samples and nine [48] Abbreviations: ANPP, 4-anilino-N-phenethylpiperidine; CBD, cannabidiol; COSY, correlation spectroscopy; HMBC, heteronuclear multiple bond correlation; HSQC, heteronuclear single quantum coherence; NMR, nuclear magnetic resonance; NPP, N-phenethyl-4-piperidinone; THC, Δ 9 -tetrahydrocannabinol; TOCSY, total correlation spectroscopy.…”
Section: Visual Interpretationmentioning
confidence: 99%
“…PHIP using benchtop NMR is a PHIP-based experiment using benchtop NMR that monitors changes in the hydrogenation process of a small amount of material. , However, the disadvantage is that the material cannot be reused, because the hydrogenated material does not return to the starting material (e.g., unsaturated carbon). To overcome the shortcoming of this technology, the suggested method is benchtop NMR using SABRE. SABRE delivers para -hydrogen’s spin order to the material, but the structure of the material does not change, so it can be used in the next reaction. Some significant studies on reaction monitoring using SABRE and benchtop NMR have been reported .…”
mentioning
confidence: 99%